Analisis Sektor Ekonomi Potensial Dalam Mendorong Pembangunan Ekonomi Daerah Di Kabupaten Trenggalek - Maulinda Lailatul Rohmah (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
This study aimed to determine the potential economic sector in Trenggalek Regency in encouraging regional economic development. The data used are Gross Regional Domestic Product data based on 2010 constant prices in 2015-2019 and data on the 2010-2019 gross regional domestic products based on regular prices for the residency of Kediri in 2015-2019. Based on the Location Quentiont analysis results, included in the fundamental and leading sectors in Trenggalek Regency are the Transportation and Warehousing sector; Electricity and Gas Procurement; Health Services and Social Activities; Financial Services and Insurance. Economic sectors that have competitive advantages and specialization are the Mining and Quarrying sector; Electricity and Gas Procurement; Water Supply, Waste Management, and Recycling; Construction; Transportation and Warehousing; Food and Drink Accommodation Providers; Information and Communication; Financial Services and Insurance; Real Estate; Government Administration, Defense, and Mandatory Social Security; Health Services and Social Activities; and Other Services. Mapping economic potential in Trenggalek Regency, the economic sectors that fall into the classification of Quadrant I, namely fast-growing and fast-growing, are the Manufacturing Industry sector; Electricity and Gas Procurement; Transportation and Warehousing; Financial Services and Insurance; Company Services; and Health Services and Social Activities.